Pengaruh Kepemimpinan Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan - Ahmad Afandi; Syaiful Bahri (Maneggio: Jurnal Ilmiah Magister Manajemen, 2020)
This research was conducted to determine how the influence of leadership on performance, how the influence of motivation on employee performance, how the influence of work discipline on employee performance and to determine the effect simultaneously on the influence of leadership, motivation and work discipline on employee performance. Asia Muslim Charity Foundation (AMCF) North Sumatra. . The population used in this study were all employees of the Asia Muslim Charity Foundation (AMCF) North Sumatra 2019, totaling 37 people. he data collection technique used a questionnaire, then analyzed the data using multiple linear regression. The results showed that partially, leadership has a positive and significant effect on performance, motivation has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, and the results show that leadership, motivation, and work discipline have a positive and significant effect. the performance of employees of the Asia Muslim Charity Foundation (AMCF) North Sumatra.